Emprendimiento Industrial Y Desarrollo Productivo Para El Crecimiento Económico Del Cantón Babahoyo. - Marquez Valero, Rosario Margot (2015)
In Ecuador a state policy is changing the productive matrix, for which there is support for the development of new factors of production, enabling Ecuadorians contribute to the socioeconomic development of the country and in turn develop its economic family. This has led to propose the development of a study entitled INDUSTRIAL PRODUCTION UP AND DEVELOPMENT FOR ECONOMIC GROWTH BABAHOYO CANTON, which aims to organize the productive activities carried out in the canton independently and in different urban and marginal sectors of this city. The study is based on a need for the capital of the province of Los Rios, this is to organize industrial activities, the same as was achieved through the creation of an industrial park, making this organization through the development of activities production in one location with all amenities and facilities such as banking, accounting, tax and information technology offices, which support small industries, it also makes it easier for potential customers to meet their needs in one place, not having to move to different places to find the goods or services you need.